Perilaku Bullying pada Anak Usia 5-6 Tahun Studi Kasus di Taman Kanak-Kanak - Wahyuni, Vitri; Pransiska, Rismareni (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
The purpose of this study was to photograph the bullying behavior carried out by children aged 5-6 years in TK Aisyiyah 29 Padang, so that the forms of bullying behavior can be identified and how the teacher attempts to deal with bullying problems at TK Aisyiyah 29 Padang. This study uses a qualitative approach with case study reseach methods. The informants chosen in this study were the teachers and principals who interacted directly with children every day. And for the subjects are childrens and teachers at TK Aisyiyah 29 Padang. Data collection teachniques used are observation, interviews, field notes, and documentation. To test the data validity is done using triangulation. The results of the study showed that the number of children’s behaviors did lead to bullying because the frequency was frequent, and efforts to deal with bullying by teachers at TK Aisyiyah 29 Padang improved after being given knowledge and insights on how to deal bullying problems.